Identification Of Oral Antidiabetic Drug Interactions In Polypharmacy Prescription Of Patients Diabetes Mellitus At Jember Hospital - Nanda Pradwitha Fariansiska; Mayasari, Shinta (Sean Institute, 2024)
Background: Diabetes mellitus (DM) is a metabolic disorder characterized by an increase in blood glucose due to decreased insulin secretion by pancreatic beta cells, disruption or insulin resistance. The rate of DM with comorbidities or complications is increasing, usually receiving more than three types of medication (polypharmacy). The potential for drug interactions in diabetes patients is still very common. There were 186 potential drug interactions, with 16.2% potentially causing hyperglycemia and the remainder causing hypoglycemia. This can be caused by the large number of drugs that are often used (polypharmacy or multiple drug therapy). Objective: to identify potential oral antidiabetic drug interactions in screening polypharmacy prescriptions for type 2 diabetes mellitus patients in hospitals. Method: This research was conducted at one of the Jember Regency Hospitals. This type of research is descriptive research with retrospective data collection. The research sample was 80 using the Slovin formula with random sampling technique. Data analysis is displayed in the form of frequencies and percentages which are then processed using Microsoft Excel and SPSS. Results: In this study it was found that male patients were (38.8%) and female were (61.3%). The age group is dominated by patients 51 – 60 years old (42.5%). Polypharmacy consisted of at most 5 drugs (45.0%), drug interactions occurred in 65 prescriptions (81.3%) with the severity of drug interactions being moderate, 38 potential events (47.5%), major, 6 potential events (7.5%). %), minor 21 potential events (26.3%), and no interaction as many as 15 potential events (18.8%). Conclusion: This study found that the potential interactions for oral antidiabetic drugs in polypharmacy screening were mostly moderate interactions (47.5%) with 38 potential events.